Premotor cortex and the conditions for movement in monkeys (Macaca fascicularis). - Halsband, U; Passingham, R (1985)
Cortical association areas direct their influence on motor cortex via premotor and supplementary motor cortex. In the present experiment premotor cortex was removed bilaterally in monkeys. The monkeys were unable to relearn a visual conditional motor task on which the correct action is specified by visual cues. It was shown that the same monkeys were unable to learn a non motor visual conditional task on which the visual cues specified which object should be chosen. It is concluded that the monkeys are only impaired when they must recall a movement from memory on the basis of a visual cue.